2014
DOI: 10.14740/wjon809w
|View full text |Cite
|
Sign up to set email alerts
|

Primary Angiosarcoma of the Breast: A Case Report and Review of Literature

Abstract: Angiosarcoma of the breast (ASB) is a rare but aggressive tumor with very poor prognosis. It is important to recognize this tumor early and to distinguish between primary and secondary ASB. While mammograms frequently miss these lesions, ultrasound and MRI show promise as imaging modalities. In spite of characteristic features described on pathology, misdiagnosis is common, with over 35% tumors initially thought to be benign. We present the case of a 32-year-old woman with a history of bilateral reduction mamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Overall, even though the radiological findings from our patient's ultrasound and MRI may not have specific diagnostic features for angiosarcoma, it did help to characterize the mass, hence leading to the correct diagnosis. There were journals which stated that fine-needle aspiration cytology and core biopsy are generally not helpful in the diagnosis of angiosarcoma as they give high false-negatives, as high as 37% [4,6,9]. This did apply in our case, where the result of the core biopsy taken by the surgical team was inconclusive with blood clots seen as the mass was highly vascular and hemorrhagic, making diagnosis difficult.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Overall, even though the radiological findings from our patient's ultrasound and MRI may not have specific diagnostic features for angiosarcoma, it did help to characterize the mass, hence leading to the correct diagnosis. There were journals which stated that fine-needle aspiration cytology and core biopsy are generally not helpful in the diagnosis of angiosarcoma as they give high false-negatives, as high as 37% [4,6,9]. This did apply in our case, where the result of the core biopsy taken by the surgical team was inconclusive with blood clots seen as the mass was highly vascular and hemorrhagic, making diagnosis difficult.…”
Section: Discussionmentioning
confidence: 75%
“…Total mastectomy is more favorable than wide local excision because of the resection margin status, as well as the high incidence of local recurrence in wide local excision as documented in most articles [3,7]. Regional axillary clearance is not necessary because they tend to metastasize hematogenously, rather than lymphogenously [3,4,7,9]. Our patient underwent total mastectomy with regional axillary clearance; however, she still developed local recurrence 6 months later.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Although Zelek et al have reported six multicentric tumors of primary breast sarcoma (7% of the cohort), the histologic types of the sarcoma could not be obtained because they were not specified [9]. Pandey et al reported a case with multiple primary angiosarcoma; however, this case had undergone bilateral reduction mammoplasty 14 years before the presentation of angiosarcoma [11]. In this previous case, preoperative MRI revealed multiple cystic structures in the entire right breast, and simple mastectomy showed multiple sections of low-grade angiosarcoma from the lower outer quadrant and mid-portion of the specimen [11].…”
Section: Discussionmentioning
confidence: 99%
“…Pandey et al reported a case with multiple primary angiosarcoma; however, this case had undergone bilateral reduction mammoplasty 14 years before the presentation of angiosarcoma [11]. In this previous case, preoperative MRI revealed multiple cystic structures in the entire right breast, and simple mastectomy showed multiple sections of low-grade angiosarcoma from the lower outer quadrant and mid-portion of the specimen [11]. Although it has been reported that radiation induces multifocal secondary angiosarcoma [6], it is not clear whether reduction mammoplasty can trigger the multifocal tumorigenesis of angiosarcoma.…”
Section: Discussionmentioning
confidence: 99%